Die vielen gesichter der krise: Archäologische und historische perspektiven auf das spätrepublikanische Italien - Maschek, D (Scripta Mercaturae, 2020)
The volume is the result of a conference under the same title, which took place on March 21 and 22, 2019 at the European University of Flensburg. A prominent field of scholars from Germany and abroad presents new research results on economy and society in the late Roman Republic and on the use of this topic in school lessons.